Evaluation of sample stability for a quantitative faecal immunochemical test and comparison of two sample collection approaches. (November 2018) - Mellen, Samantha; de Ferrars, Maria; Chapman, Claire; Bevan, Sarah; Turvill, James; Turnock, Daniel
Background: Faecal immunochemical testing is increasingly being used to triage symptomatic patients for suspected colorectal cancer. However, there are limited data on the effect of preanalytical factors on faecal haemoglobin when measured by faecal immunochemical testing. The aim of this work was to evaluate the stability of faecal haemoglobin in faeces and to compare two methods of faecal haemoglobin sampling for faecal immunochemical testing. Methods: Six patients provided faeces for faecal haemoglobin measurement which were transferred into specialized collection devices at baseline and at 1, 2, 3 and 7 days after storage at either room temperature or 4°C. A total of 137 patients returned both faeces transferred into the specialized collection device and faeces in a standard collection pot. A quantitative immunoturbidometric method was used to measure faecal haemoglobin and results were compared categorically. Discrepant results were assessed against diagnosis. Results: Faecal haemoglobin concentration declined rapidly within a day of storage at room temperature but results remained ≥10 μg Hb/g faeces in 5/6 patients after two days. A faecal haemoglobin result ≥10 μg Hb/g faeces was obtained in 4/6 patients after storage for seven days at 4°C. Results obtained when patients used specialized collection devices were significantly different from results obtained when faeces was transferred into the specialized collection device in the laboratory. Conclusion: There is considerable heterogeneity in the sample stability of faecal haemoglobin; therefore, samples should be transferred rapidly into specialized collection devices to prevent false-negative results. Use of collection devices by patients can lead to false-positive results compared with their use in a laboratory.